Ignacio Pirovano y el coleccionismo de vanguardia - Talía Bermejo (Estudios Curatoriales, 2014)
Well into the 40s, Ignacio Pirovano put aside the repertoires of artists who where acclaimed by the local collectionism and took a risk with non-representational avant-garde art. He selected representatives from concrete groups and from sectors of the geometric abstractionism when these streams embodied the most radical renovation in the field. Through this path and with a prolific public activity in multiple roles as collector, painter, manager and entrepreneur, he managed to arise as a model for alternative consumption in the selections that were visible in Buenos Aires between 1950 and 1965. The purpose of this article is to analyse the first years in which this pool was gathered as that was the time when Pirovano consolidated a decisive change in Argentinean collectionism, even thought his purchases continued up to the 70s. In this sense, he represents a pragmatic case worth observing for the dynamic nature and the possibilities of transformation of a private collection, as well as the public acknowledgment of its development and the institutional projections feeding a significant portion of personal decisions.